YIELD IMPROVEMENT OF EGUSI MELON (COLOCYNTHIS CITRILLUS L.) THROUGH INTERGENERIC HYBRIDIZATION WITH WATERMELON (CITRILLUS LANATUS L.) - V. O. Ogbu; P. E. Ogbonna; V. N. Onyia; E. C. Okechukwu (Journal of Animal and Plant Sciences, 2016)
This research was aimed to improve the productivity of ‘egusi’ melon through generic hybridization with watermelon. The experiment was carried out in the Department of Crop Science, University of Nigeria, Nsukka, Nigeria. Parental seeds of ‘egusi’ melon accessions from Taraba (Tar), Abakaliki (Abk), Nsukka (Nsk) and watermelon varieties from Kolos (Kol) and Koalack (Koa) were used for the study. Hybrids from all possible cross combinations between parents of ‘egusi’ melon and watermelon were generated using diallel method of selection. The parents, Kolos and Taraba were the best general combiners for yield and growth attributes, respectively. Crosses; Abk x Nsk, Abk x Koa, Tar x Kol and Kol x Abk were good specific combiners for all the traits measured. Four and three clusters were obtained in the F1 and F2 progenies, respectively in all the traits combined. The high diversity obtained underlies prospects for improvement of ‘egusi’ melon through intergeneric hybridization.
Keywords: Genetic diversity; general combining ability; specific combining ability; hybrids